2009
DOI: 10.1007/s11829-009-9083-6
|View full text |Cite
|
Sign up to set email alerts
|

Is a mango just a mango? Testing within-fruit oviposition site choice and larval performance of a highly polyphagous fruit fly

Abstract: For fruit flies, fully ripe fruit is preferred for adult oviposition and is superior for offspring performance over unripe or ripening fruit. Because not all parts of a single fruit ripen simultaneously, the opportunity exists for adult fruit flies to selectively choose riper parts of a fruit for oviposition and such selection, if it occurs, could positively influence offspring performance. Such fine scale host variation is rarely considered in fruit fly ecology, however, especially for polyphagous species whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 48 publications
3
16
0
Order By: Relevance
“…A similar result was reported by Rattanapun et al . (), who found that adult emergence from pupae that had developed from mature green mango was only half of that of pupae originating from fully ripe mango. Potential limits in larval di et al so appear to flow on to the subsequent adults with, for example, no eggs collected from the 23 female flies reared from grapefruit.…”
Section: Discussionmentioning
confidence: 99%
“…A similar result was reported by Rattanapun et al . (), who found that adult emergence from pupae that had developed from mature green mango was only half of that of pupae originating from fully ripe mango. Potential limits in larval di et al so appear to flow on to the subsequent adults with, for example, no eggs collected from the 23 female flies reared from grapefruit.…”
Section: Discussionmentioning
confidence: 99%
“…2001; Fontellas‐Brandalha and Zucoloto 2004; Hannah and Zalom 2008; Rattanapun et al . 2010), positive preference/performance relationships have been demonstrated, but this relationship is not universal across frugivorous tephritids (Fitt 1986; Fernandes‐Da‐Silva and Zucoloto 1993; Balagawi et al . 2013) and should not be automatically assumed.…”
Section: Discussionmentioning
confidence: 99%
“…Prokopy and Vargas (1996) believe that epicarp thickness of citrus fruits could be an important criterion in infestation of fruit flies. Thus, the host range of tephritid fruit flies may be restricted by the ability of the insect to penetrate the peel of the host fruit (Rattanapun et al, 2009(Rattanapun et al, , 2010. Thus, this study investigated oviposition of A. fraterculus and C. capitata and its relation with the pericarp of citrus fruits.…”
Section: Introductionmentioning
confidence: 99%